Dissociated Time Course of Muscle Damage Recovery Between Single- and Multi-Joint Exercises in Highly Resistance-Trained Men. Issue 9 (September 2015) - Soares, Saulo; Ferreira-Junior, João B.; Pereira, Maria C.; Cleto, Vitor A.; Castanheira, Rafael P.; Cadore, Eduardo L.; Brown, Lee E.; Gentil, Paulo; Bemben, Michael G.; Bottaro, Martim
Abstract : Abstract: Soares, S, Ferreira-Junior, JB, Pereira, MC, Cleto, VA, Castanheira, RP, Cadore, EL, Brown, LE, Gentil, P, Bemben, MG, and Bottaro, M. Dissociated time course of muscle damage recovery between single- and multi-joint exercises in highly resistance-trained men. J Strength Cond Res 29(9): 2594–2599, 2015—This study compared the time course of elbow flexor muscle recovery after multi- and single-joint exercises in highly resistance-trained men. Sixteen men (24.5 ± 5.5 years) performed, in a counterbalanced order, 8 sets of 10 repetition maximum (RM) unilateral seated row exercise and 8 sets of 10RM unilateral biceps preacher curl exercise using the contralateral arm. Maximum isometric peak torque (PT) and delayed onset muscle soreness (DOMS) were recorded at baseline (pre), 10 minutes, 24, 48, 72, and 96 hours after each exercise protocol. There was a significant decrease ( p ⩽ 0.05) in elbow flexor PT 10 minutes after both the multi- and single-joint exercise sessions. However, PT decrease was greater after single-joint (26.8%) when compared with multi-joint (15.1%) exercise ( p ⩽ 0.05). In addition, elbow flexor PT was lower (8.4%) than baseline 24 hours after the single-joint exercise ( p < 0.01), whereas PT returned to baseline 24 hours after the multi-joint exercise. Compared with baseline, DOMS increased at 24, 48, and 72 hours after single-joint exercise ( p ⩽ 0.05). However, DOMS returned to baseline levels after 72 hours after multi-joint exercise. In addition, DOMS after single-joint exercise was greater ( p ⩽ 0.05) than after multi-joint exercise at 24, 48, and 72 hours after exercise. Our data suggest that after a resistance training session, highly resistance-trained men experience dissimilar elbow flexor strength recovery between single-joint and multi-joint exercises. Likewise, elbow flexor DOMS is greater and takes longer to recover after single-joint exercise.